2017
DOI: 10.1177/1745691616667925
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of Consensually Nonmonogamous Relationships

Abstract: We proposed that the premise that monogamy is the exemplary form of romantic partnership underlies much theory and research on relationship quality, and we addressed how this bias has prompted methodological issues that make it difficult to effectively address the quality of nonmonogamous relationships. Because the idea that consensually nonmonogamous (CNM) relationships are functional (i.e., satisfying and of high quality) is controversial, we included a basic study to assess, in a variety of ways, the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
112
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 126 publications
4
112
1
6
Order By: Relevance
“…We found no differences in testing and documented significantly greater condom use among participants in open relationships for anal intercourse. Based on a comprehensive review of the literature, Rubel and Bogaert (2015) found that individuals in CNM partnerships tended to report equal or greater relationship satisfaction relative to those in monogamous partnerships (see also Conley, Matsick, Moors, & Ziegler, 2017). In contrast, we documented lower reported relationship happiness and sexual satisfaction among individuals in open relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no differences in testing and documented significantly greater condom use among participants in open relationships for anal intercourse. Based on a comprehensive review of the literature, Rubel and Bogaert (2015) found that individuals in CNM partnerships tended to report equal or greater relationship satisfaction relative to those in monogamous partnerships (see also Conley, Matsick, Moors, & Ziegler, 2017). In contrast, we documented lower reported relationship happiness and sexual satisfaction among individuals in open relationships.…”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial literature on other sexual minority populations, including but not limited to those in open relationships and other CNM partnerships, that indicates such effects (e.g., Clair, Beatty, & Maclean, 2005; Conley et al, 2012a, 2012b; Jones & King, 2014). Moreover, stigmatizing experiences and relationship quality vary considerably across and within different forms of consensual nonmonogamy (Conley et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…One solution to this problem is to alter expectations about romantic relationships and outsource needs. Indeed, it has been proposed that couples could alter their expectations about relationships; that is, rather than relying on one partner to meet both erotic and nurturant needs, individuals could outsource their needs to other relationships, diversifying their need fulfilment across multiple romantic or sexual partners (Conley, Matsick, Moors, & Ziegler, 2017;Conley & Moors, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…1,4 These individuals face great stigma and are often patholo gized based on inaccurate assumptions. 5 However, several studies have failed to find differences in relationship satisfaction and other indices of relationship functioning between monoga mous and consensually nonmonogamous relationships. 2,5 Furthermore, rates of sexually transmitted infections (STIs) are comparable across consensually nonmonogamous and monoga mous populations.…”
mentioning
confidence: 99%
“…5 However, several studies have failed to find differences in relationship satisfaction and other indices of relationship functioning between monoga mous and consensually nonmonogamous relationships. 2,5 Furthermore, rates of sexually transmitted infections (STIs) are comparable across consensually nonmonogamous and monoga mous populations. 6 Despite this, the majority of individuals who practise consensual nonmonogamy have experienced discrimina tion, 7 a phenomenon associated with higher levels of psycho logical distress and poorer health outcomes.…”
mentioning
confidence: 99%